Analisis kualitas website Dewan Perwakilan Mahasiswa Universitas Telkom menggunakan WebQual 4.0 - Mochammad Faizal (Jurnal Manajemen Maranatha, 2019)
Telkom University is a tertiary institution that has a variety of student organizations as a place to channel and develop the potential of students. Student Council of Telkom University Student Family or commonly abbreviated as DPM Kema Tel-U is one of the student organizations at Telkom University that has several functions such as supervision, legislation, aspirations, and budget. The involvement of Telkom University students is needed in carrying out these four functions, and one of the methods used is to carry out publication activities related to various activities that will be or are being held. However, Kema Tel-U DPM has not been able to maximize the website which is considered to be the main channel in information dissemination activities. To answer these problems, researchers will conduct a literature study to obtain various relevant theories, modify the WebQual 4.0 instrument that is tailored to the research needs, then conduct questionnaires to 120 students of Telkom University. The collected data will be analyzed using the suitability level method and importance-performance analysis using the SPSS version 25 application to answer the research problem. This study aims to determine the level of user satisfaction with the DPM Kema Tel-U website, as well as identify variables that need to be addressed to improve the quality of research objects by their priorities. The results obtained are the priority order for improving a website maintained by the Student Representative Council of Telkom University, and a new instrument derived from modified WebQual instruments 4.0. This research can be a reference to assess other websites that are similar to the DPM Kema Tel-U website.